2013
DOI: 10.1155/2013/590652
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spinal Stenosis Has a Negative Impact on Quality of Life Compared with Other Comorbidities: An Epidemiological Cross‐Sectional Study of 1862 Community‐Dwelling Individuals

Abstract: Lumbar spinal stenosis (LSS) is common in the elderly. However, there have been few reports on its impact on quality of life (QoL) in community-dwelling individuals. The purpose of this study was to clarify how symptomatic LSS affects QoL at the community level. A total of 1862 people (697 males and 1165 females, most subjects were between 40 and 85 y.o.) agreed to participate and were interviewed. The presence of symptomatic LSS was assessed by a specially designed questionnaire. The Medical Outcomes Study 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 35 publications
3
96
0
6
Order By: Relevance
“…Koji et al [7] investigated the effect of comorbidities on quality of life in their study and found that lumbar spinal stenosis was the most detrimental compared to comorbidities such as knee and hip osteoarthritis, cardiovascular disease, cerebrovascular disease, respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Koji et al [7] investigated the effect of comorbidities on quality of life in their study and found that lumbar spinal stenosis was the most detrimental compared to comorbidities such as knee and hip osteoarthritis, cardiovascular disease, cerebrovascular disease, respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased walking distance significantly influences daily life, and people with LSS report a lower quality of life than people with osteoarthritis in the knee and hip (32). In people 60 years and older, diabetes mellitus, urological disorders, and osteoarthritis/fracture have been reported as comorbidities, and depressive symptoms are associated with LSS (33). Screening for these associated factors helps to draw up a tailored intervention.…”
Section: Lumbar Spinal Stenosismentioning
confidence: 99%
“…The incidence rate is 1.70% to 8.00% in people over age 50 years, and is higher in females than males [1]. The disease can occur in the central canal, lateral recess, or intervertebral foramen, and the most common site is the narrow entrance zone of the lateral recess [2].…”
Section: Introductionmentioning
confidence: 99%